2021
DOI: 10.3390/cells10051115
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Free Phosphatidylcholine Levels in Cerebrospinal Fluid Distinguish Bacterial from Viral CNS Infections

Abstract: The identification of CSF biomarkers for bacterial meningitis can potentially improve diagnosis and understanding of pathogenesis, and the differentiation from viral CNS infections is of particular clinical importance. Considering that substantial changes in CSF metabolites in CNS infections have recently been demonstrated, we compared concentrations of 188 metabolites in CSF samples from patients with bacterial meningitis (n = 32), viral meningitis/encephalitis (n = 34), and noninflamed controls (n = 66). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Investigations based on metabolomics may have a role in distinguishing neuroinflammation from infection [57]. Of particular interest are lipid-based biomarkers, such as free phosphatidyl choline levels [58,59]. The CNS contains high concentrations of lipids, including phosphatidyl choline, ceramides, and sphingomyelins, all of which have important roles in the inflammatory response.…”
Section: Csf Features Of Infectionmentioning
confidence: 99%
“…Investigations based on metabolomics may have a role in distinguishing neuroinflammation from infection [57]. Of particular interest are lipid-based biomarkers, such as free phosphatidyl choline levels [58,59]. The CNS contains high concentrations of lipids, including phosphatidyl choline, ceramides, and sphingomyelins, all of which have important roles in the inflammatory response.…”
Section: Csf Features Of Infectionmentioning
confidence: 99%
“…Therefore, further efforts are needed to dissect the co-metabolism of host and pathogen. Moreover, while our work focused on polar metabolites, it has been reported that certain lipid classes, such as phosphatidylcholines, sphingolipids and ceramides, play an important role in CNS infection [52,53]. Multi-omics characterization of CSF, as well as peripheral blood are expected for an integrated and detailed regulatory landscape regarding CNS infection.…”
Section: Targeted Metabolomic Analysis For Semi-quantitative Verification and Pathway Analysismentioning
confidence: 99%
“…We have previously applied a targeted metabolomics approach to measure 188 small molecules in CSF from 221 patients with infectious, autoimmune, and non-in ammatory CNS disorders. In previous publications we reported the identi cation of accurate biomarkers for CNS involvement in varicella-zoster virus reactivation (10), for enterovirus meningitis in patients without CSF pleocytosis (11), and for the differentiation between bacterial and viral meningitis (12,13). We have now expanded the analysis of this cohort to screen for CSF metabolite biomarkers that can accurately distinguish between viral CNS infections and autoimmune meuroin ammation and may reveal pathophysiological differences between the two.…”
Section: Introductionmentioning
confidence: 97%